HUBUNGAN ANTARA RELIGIUSITAS DENGAN KECEMASAN AKADEMIK PADA SISWA MADRASAH ALIYAH NEGERI - Fitri Ukhtia; Iredho Fani Reza; Zaharuddin Zaharuddin (Psikis : Jurnal Psikologi Islami, 2016)
Students often experience anxiety at the moment are in academic situations. This study examined the  correlation  between  religiosity  and  academic  anxiety  in  students  MAN  in  one  of  the  cities  of Palembang. The independent variables in this study are religiosity, while the dependent variable is the  academic  anxiety.  The  hypothesis  put  forward  is  no  relationship  between  religiosity  and academic anxiety in students. The sampling technique in this study using a random cluster sampling technique which produces 319 students as respondents. Data collection methods used in this study a scale  of  religiosity  that  is  made  by  researchers  using  the  dimensions  of  religiosity  based  on  the opinions  Jamaluddin  Ancok  and  Fuad  Nashori  Suroso  consisting  of  five  dimensions.  Then  the anxiety scale made by the academic researchers used a Hamilton anxiety symptoms based on the opinion  that  consists  of  14  symptoms.  Data  analysis  methods  used  to  test  the  hypothesis  of  this research  is  simple  regression  analysis  that  generates  a  correlation  coefficient  of  p  =  0.000  (p <0.05), which showed a negative correlation between religiosity and academic anxiety in students. The results of the donations given to anxiety academic religiosity of 16.8% and the rest influenced by other factors not disclosed in this study.